Antioxidant and Anticancer Activity of Dillenia serrata Thunb Ethanol Extract Against MCF-7 Breast Cancer Cell Line - Rahmawati, Rahmawati; Zulkifli, Zulkifli; Nuringtyas, Tri Rini; Jenie, Riris Istighfari; Nugroho, Laurentius Hartanto (Indonesian Journal of Cancer Chemoprevention, 2022)
Women’s breast cancer incidence rate in Indonesia ranks number one with 12 per 100,000 cases, with luminal A as the dominant subtype. Currently, chemotherapeutic agents have limitations that lead to inefficiencies in therapy, therefore it is necessary to develop more effective and efficient chemopreventive agents. Plant secondary metabolites can provide pharmacological effects that can be used as chemoprevention agents. Secondary metabolites of D. serrata may have pharmacological effects as antioxidants and cytotoxic. This study aims to determine the antioxidant properties and cytotoxic activity of D. serrata ethanolic extract on the MCF-7 breast cancer cell line. The leaves of D. serrata were macerated, while the bark and root samples were refluxed with 96% ethanol as solvent. All extracts were evaporated with a rotary evaporator. Qualitative evaluation of the phytochemical content of leaf ethanolic extract, bark ethanolic extract, and root ethanolic extract was done using the standard tube test method. The antioxidant assay was carried out using the DPPH. The cytotoxic activity was determined in vitro using an MTT assay against the MCF-7 cell line with a series of concentrations from 12.5–400 μg/mL. Doxorubicin was the positive control treated at a 3.125–100 μg/mL concentration. The antioxidant activity showed that leaf extract had the highest antioxidant activity, followed by root and bark extract, with IC50 values of 95.66, 270.5, and 335.96 ppm, respectively. Leaf ethanolic extract and root ethanolic extract’s cytotoxic ability is considered moderate cytotoxic with IC50 values of 493.17 and 229.82 μg/mL, respectively. Amongst the ethanolic extract from the leaf, bark, and root of D. serrata, the leaf ethanolic extract has the best anti-oxidant activity and the bark ethanolic extract was the most cytotoxic one against MCF-7 cells.Keywords: Antioxidant, Cytotoxic, Dillenia serrata, MCF-7.